2013
DOI: 10.1017/jfm.2013.230
|View full text |Cite
|
Sign up to set email alerts
|

Mode C flow transition behind a circular cylinder with a near-wake wire disturbance

Abstract: The three-dimensional transition of the flow behind a circular cylinder with a near-wake wire disturbance has been investigated experimentally. The asymmetric placement of a wire in the near-wake region of the cylinder causes an unnatural mode of shedding to occur, namely mode C. We performed flow visualization and particle image velocimetry (PIV) experiments to investigate the influence of the wire on various properties of the flow, such as the dynamics of the streamwise secondary vortices. Experiments were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…Its nominal spanwise wavelength was λ z /d ≈ 1.1 at α = 1.7, but increased significantly with decreasing rotation rate. This mode has similar characteristics to the subharmonic mode C observed in the wakes of a torus (Sheard et al 2005a), and of a cylinder disturbed by a thin wire (Zhang et al 1995;Yildirim et al 2013). Furthermore, a complex interaction with mode B took place for α 1.0.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Its nominal spanwise wavelength was λ z /d ≈ 1.1 at α = 1.7, but increased significantly with decreasing rotation rate. This mode has similar characteristics to the subharmonic mode C observed in the wakes of a torus (Sheard et al 2005a), and of a cylinder disturbed by a thin wire (Zhang et al 1995;Yildirim et al 2013). Furthermore, a complex interaction with mode B took place for α 1.0.…”
supporting
confidence: 62%
“…The wavelength was λ z /d = 1.7 in simulations, and λ z /d ≈ 2 in experiments. Yildirim, Rindt & van Steenhoven (2013) extended these experiments and demonstrated the period doubling of the main shedding cycle caused by mode C. Sheard, Thompson & Hourigan (2003b, 2005a observed a subharmonic mode (λ z /d = 1.9) in simulations, and experiments (Sheard et al 2005b), in the wake of a torus aligned normal to the direction of flow. Depending on the aspect ratio of the torus, the mode became unstable at a Reynolds number lower than the well-known modes A and B.…”
Section: Introductionmentioning
confidence: 75%
“…For the non-rotating cylinder, the presence of a wire of diameter D/100 upstream does not trigger the mode C instability, and does not suppress mode A and mode B instabilities, at least at Re = 275, well above the critical Reynolds numbers for the mode A and B transition. This is similar to the situation for the wire placed downstream (Zhang et al 1995;Yildirim et al 2013b).…”
Section: Comparison With the Experimental Findingssupporting
confidence: 72%
“…Further details of the particular spectral-element implementation can be found in Ryan, and Thompson et al (2006). A secondary validation check was undertaken to confirm that the subharmonic mode observed in the studies of Zhang et al (1995), Yildirim et al (2013b) can indeed be observed when a wire of diameter d = D/100 is placed downstream of a non-rotating cylinder for Re 300. Shown in figure 4 are perturbation contours of spanwise vorticity at Re = 200, where the maximum growth rate occurs at λ/D 1.4.…”
Section: Methodsmentioning
confidence: 99%
“…Subharmonic modes have also been observed when the wake symmetry is altered, as in the flow past rings (Sheard et al, 2005b(Sheard et al, , 2004a, and inclined square cylinders (Sheard et al, 2009;Sheard, 2011). In addition, such modes have also been observed in a non-rotating cylinder wake when a wire was placed downstream of the cylinder (Zhang et al, 2005;Yildirim et al, 2013) or upstream (Rao et al, 2015b).…”
Section: Introductionmentioning
confidence: 98%